Stimulation of TRPV1 by Green Laser Light. (17th December 2012) - Gu, Quanbao; Wang, Lina; Huang, Fang; Schwarz, Wolfgang
Abstract : Low-level laser irradiation of visible light had been introduced as a medical treatment already more than 40 years ago, but its medical application still remains controversial. Laser stimulation of acupuncture points has also been introduced, and mast-cells degranulation has been suggested. Activation of TRPV ion channels may be involved in the degranulation. Here, we investigated whether TRPV1 could serve as candidate for laser-induced mast cell activation. Activation of TRPV1 by capsaicin resulted in degranulation. To investigate the effect of laser irradiation on TRPV1, we used the Xenopus oocyte as expression and model system. We show that TRPV1 can functionally be expressed in the oocyte by (a) activation by capsaicin (K 1 / 2 = 1.1 μ M), (b) activation by temperatures exceeding 42°C, (c) activation by reduced pH (from 7.4 to 6.2), and (d) inhibition by ruthenium red. Red (637 nm) as well as blue (406 nm) light neither affected membrane currents in oocytes nor did it modulate capsaicin-induced current. In contrast, green laser light (532 nm) produced power-dependent activation of TRPV1. In conclusion, we could show that green light is effective at the cellular level to activate TRPV1. To which extend green light is of medical relevance needs further investigation.